Wagnis und Wahrscheinlichkeit: Religionsphilosophische Reflexionen zum Begriff des Risikos - Klinge, Hendrik (Theologische Rundschau, 2021)
This paper attempts to provide a philosophical analysis of the concept of risk by stressing its religious significance. After a few brief considerations regarding contemporary ethics of risk, I examine two prominent philosophical texts that deal with the concept of risk from a religious point of view. In discussing Pascal's Wager, I establish the idea that it is always rational to trust God, since the certitude of faith's object is enough to render all considerations about probability meaningless. Hence, a life devoted to religion is immensely attractive, since it does not have in store the frustrations of every-day-life. The famous argument given in James' The Will to Believe is quite similar, but it can be accentuated differently. According to James, the believer has the right to hold on to his belief, even though he cannot prove its content to be true. This permission is due to the fact that the risk of losing the truth is not always preferable to chance of error. Nevertheless, insofar as the believer always runs the risk of getting deceived in the end, it takes courage to believe in God. By contrast, conspiracy theorists act in a cowardly way, since they risk nothing. In times of uncertainty, religion can help to live both a meaningful and a courageous life, because faith's certitude does not depend on probabilities, neither does it require the support of 'alternative' facts. To put it in a nutshell, religion is a risk always worth taking.